PENGARUH KONDISI EKONOMI KELUARGA TERHADAP TINGKAT PENDIDIKAN ANAK DI DESA SIHABORGOAN BARUMUN - Rambey, Mara Judan (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
This study aims to find out whether there is a significant influence between family economic conditions on children’s education levels. For this reason, this study includes two variables, namely family economic conditions as variable X and the level of education of children variable Y. This research was conducted at Sihaborgoan Barumun Jl. Binanga, Barumun Tengah District, Padang Lawas Regency. The population in this study is the entire sihaborgoan Barumun village community, and the sampling method used in this study is incidental sampling or coincidentally, the sample taken in this study is as many as 30 people. In analyzing the data, guttman scale method questionnaires were used for family economic conditions (variable X) and variable child education level (Y). Then the results are analyzed with inferential analysis. From the results of the analysis obtained the average value of family economic conditions is 84.5 in the category of "Excellent", the average value of the child’s education level is 82.33 in the category of "Excellent". Based on the t test conducted on table 16 shows that the calculated value is 5,800 with a confidence level of 95% or an error rate of 5% thus 5,800>1,699 then H0 rejected Ha accepted. Based on these results it can be concluded that the hypothesis is acceptable. This means that there is a significant influence between the Economic Condition of the Family on the Level of Children’s Education in Sihaborgoan Barumun Village.